Addressing Performance Tensions in Multiteam Systems: Balancing Informal Mechanisms of Coordination within and between Teams - Ziegert, Jonathan C.; Knight, Andrew P.; Resick, Christian J.; Graham, Katrina A. (Academy of Management Journal, 2022)
Due to their distinctive features, multiteam systems (MTSs) face significant coordination challenges—both within component teams and across the larger system. Despite the benefits of informal mecha...